DEVELOPING INFORMATION TECHNOLOGY CAPABILITIES FOR HIGH SCHOOL STUDENTS IN HO CHI MINH CITY - Doai Hoang Duc, Nguyen Anh Ngoc, Phan Thanh Huan*; Huynh Thi Chau Ai (Tạp chí Khoa học, 2024)
Information technology competency is the ability to apply information technology and digital tools to support and improve the quality of teaching and learning in different subjects. Through teaching activities using information technology, all subjects contribute to developing this capacity. To meet the needs of developing students' information technology capabilities (mainăng lựcy the ability to use information technology) in teaching subjects, first of all, teachers are proficient in information technology skills and enhance the application of information technology in the teaching process. Teachers at high schools in Ho Chi Minh City were surveyed on the issue of developing the ability to use information technology through teaching activities in the current context. From there, propose solutions to improve the effectiveness of information technology application in teaching, improving the quality of teaching and developing information technology capacity for students in the current context of digitalization of education and training.